KORUPSI, PERTUMBUHAN EKONOMI DAN KEMISKINAN DI INDONESIA - I Ketut Patra, Junaidi (Universitas Muhammadiyah Surakarta, 2018)
Some countries have been faced to corruption stage. Especially developing region, corruption has became a disaster humankind and occur a global issue, because it is very disturbing cycle of the world economy. In many cases corruption related to financial report manipulation. One of the factor fraud rate is accounting have leave religion aspect in their report. A revolution of solution must be born in the globe. to reduces and combating the level of corruption, but on the other hand accounting makes corruption becomes more fertile. This research uses the literature approach and is expected to be one of the concepts for future research in conducting research on the prevention of corruption for accounting sector. Based on literature study we found that the approach to culture and religiosity in Indonesia will be more effective in preventing corruption. This is caused by the people of Indonesia, which consists of many tribes, cultures, beliefs and religions.